Integrating Digital Literacy and Character Education in the Society 5.0 Era: A Conceptual Framework for Achieving Sustainable Quality Education (SDG 4) - Rosmiati Rosmiati (International Forum of Researchers and Lecturers, 2026)
The transition toward Society 5.0 a human-centred society that fuses cyberspace and physical space has positioned digital literacy at the centre of educational reform, yet the same acceleration of technology exposes learners to misinformation, cyberbullying, and the erosion of ethical values, revealing that digital skills without strong character are insufficient for sustainable development. This review addresses the problem that digital literacy and character education are frequently pursued as separate agendas, and it aims to construct an integrative conceptual framework linking the two to Sustainable Development Goal 4 (SDG 4) on inclusive and equitable quality education. Using a narrative literature review and conceptual analysis, theoretical and policy sources on digital literacy, character education, Society 5.0, and SDG 4 were examined and synthesised thematically. The analysis shows that the two constructs share the common goal of forming learners who act competently and responsibly, and that their integration converges on the concept of responsible digital citizenship. The proposed framework positions the school, teacher, and curriculum as enabling inputs; the simultaneous cultivation of digital competence and character values as the learning process; digitally literate and ethically grounded learners as the output; and sustainable quality education as the outcome. The framework offers practical guidance for curriculum developers, teachers, and policymakers seeking to align education in the Society 5.0 era with the SDG 4 agenda.